The Impact of Inflation on Economic Growth in West Sumatra - Dwi, Gebi Sintia; Leli, Maisarah; Ningsih, Rahayu; Nuraiman, Nuraiman (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This research is important because uncontrolled inflation can reduce economic growth, weaken purchasing power, and increase inequality in West Sumatra. From an Islamic economic perspective, price stability is related to justice and welfare (falah), so this research is relevant for policy basis. This research aims to analyze the effect of inflation on economic growth in West Sumatra for the period 1985–2024 using a time series approach and an Islamic economics review. Secondary data were collected through documentation from official publications of the Central Statistics Agency (BPS) and analyzed using EViews through stationarity tests, classical assumption tests, and simple linear regression. The results show that inflation becomes stationary after differencing once, and the regression model meets the classical assumptions (no symptoms of normality, autocorrelation, and heteroscedasticity). Inflation is proven to have a significant negative effect on economic growth, with a p-value of 0.0000 <0.05. This indicates that increasing inflation tends to reduce economic growth in West Sumatra. In the perspective of Islamic economics, price stability is part of an effort to maintain economic justice and social welfare (falah) so that uncontrolled inflation can disrupt income distribution and reduce people's purchasing power. Therefore, controlling inflation is important not only economically, but also to realize the values ​​of justice in the Islamic economic system